“How can you be allergic to peas?” – A qualitative study to explore food handler’s knowledge, attitudes and understanding of food allergens - Allen, David; Mitchell, Graeme; Pascucilla, Michael (Sanitarno inženirstvo International Journal of Sanitary Engineering Research, 2019)
Abstract It is clear that there is an increasing proportion of the United Kingdom (UK) population who are suffering with food allergies and this combined with an increase in the frequency of eating away from home (where there is less control over the content of food) poses a significant risk. In December 2014, the European Union (EU) introduced legislation which aimed to ensure that customers with food allergens could make informed choices and safely consume food, without the risk of a potentially life-threatening reaction. The research used semi-structured interviews with staff from a BCB, located in the North West of the UK, as the aim of the research was to explore food handlers’ knowledge, attitudes and understanding of food allergens. The findings of the semi-structured interviews identified five themes: E-learning training programmes: the staff felt that these were ineffective and did not take into account individual learning styles. Responsibility: there is a lack of clarity as to who is responsible, with staff believing the key responsibility lies with the customer. Communication: similarly, communication, both within the kitchen and within the company was not clear and likely to give rise to confusion. Need to make a profit: the staff felt that the drive for profit meant that customer safety was being compromised, especially when staff numbers were reduced. Staff awareness: the staff felt confident in their own ability to prepare a safe meal but indicated that staff may be dismissive towards claims of allergen sufferers. In conclusion, these themes illustrate that a significant risk exists for allergen suffers, who rely upon the knowledge, attitudes and understanding of BCB staff to ensure their meals are safely prepared.
0 citations (Crossref) [2023-10-31]
Keywords: dept.pch; peer-reviewed